Petroleum source rocks characterization and hydrocarbon generation of the Upper Jurassic succession in Jabal Ayban field, Sabatayn Basin, Yemen - Nabil M. Al-Areeq; Marwan A. Al-Badani; Adel H. Salman; Mohammed A. Albaroot (Egyptian Journal of Petroleum)
The Upper Jurassic samples of Jabal Ayban field, Sabatayn Basin, western Yemen were used to determine the source rock characteristics and petroleum generative potentials. Based on organic geochemical analysis, the Upper Jurassic source rocks have variable TOC content in the range of 0.82–13 wt%, indicating a fair to very good source rock generative potential. The bulk geochemical results showed that Safer Member contains Type III kerogen grading to mixed Type II–III, while the Lam and Meem members displaying generally Type II, mixed Type II–III and Type III kerogens, which have the ability to generate mixed oil and gas accumulations under thermal maturation level. Vitrinite reflectance in the range (0.35–0.78% Ro) and Tmax in the range (411–445 °C), generally proving that the Meem source rocks have sufficient thermal maturity for hydrocarbon-generation, whereas the Lam and Safer are immature source rocks. 1D basin modelling was performed to analyse the hydrocarbon generation and expulsion history of the study area. Calibration of the model with measured VR (% Ro) and (BHT) data shows that the paleo-heat-flow was high at Late Jurassic. The burial/thermal history models indicate that the source rocks in the Lam and Safer members are immature source rocks and the peak oil generation has not been reached yet. The models also indicate that the early hydrocarbon generation (0.64% Ro) in the Meem source rock occurred during late Jurassic at 150 Ma and the main hydrocarbon generation (0.79% Ro) has been reached approximately at 146 Ma. Therefore, the Meem Member can be consider as generative potentials of prospective source rock horizons in Jabal Ayban field, Sabatayn Basin. Keywords: Upper Jurassic source rocks, Thermal maturity, Hydrocarbon generation modeling, Jabal Ayban field, Sabatayn Basin, Yemen